PENGEMBANGAN LKPD BERBASIS HOTS DAN AJARAN KI HADJAR DEWANTARA PADA PEMBELAJARAN MATEMATIKA KELAS IV SD - Sulistyawati, Sinta; Arcana, I Nyoman; Trisniawati, Trisniawati (Universitas Sarjanawiyata Tamansiswa, 2020)
This research aims to: (1) develop Learners Worksheets (LKPD) based on Higher Order Thinking Skills (HOTS) and the teachings of Ki Hadjar Dewantara (Tri N) in mathematics learning in grade IV elementary school and the materials of flat shape, (2) to test the feasibility of the Learners Worksheet created in this research. This research uses Research and Development (R&D) and uses the ADDIE development model. The subject of the research was the students of fourth-graders A and B of SD Winongo. The expert validation questionnaire and the student response questionnaire were used as the instruments of the research. Product eligibility is based on validator results. The results of the research are the product LKPD products based on HOTS and the Teachings of Ki Hadjar Dewantara on the flat shape material of class IV elementary school. Based on the validation research, LKPD products are suitable to use with an average of 78.6. Based on the result of the learner's responses indicate that the LKPD is suitable to use with an average of 48.9. It can be concluded that the development of the HOTS-based LKPD and the Teachings of Ki Hadjar Dewantara in the fourth-grade mathematics learning of elementary schools, is suitable and practical to use.Ã‚Â